Addressing the childhood cancer crisis in sub-Saharan Africa - Lubega, Joseph; Chirande, Lulu; Atwine, Barnabas; Davidson, Alan; Kashaigili, Heronima J; Kanyamuhunga, Aimable; Langat, Robert K; Munube, Deogratias; Mzikamanda, Rizine; Namazzi, Ruth; Nzamu, Irene; Akullo, Anne; et al. (The Lancet Oncology, 2023)
Sub-Saharan Africa is facing a childhood cancer crisis. Annually, nearly 90% of the more than 100 000 children who develop cancer in sub-Saharan Africa die. By contrast, 85% of paediatric patients with cancer survive in high-income countries, where advanced paediatric cancer care is available. Additionally, the burden of paediatric cancer in sub-Saharan Africa is compounded by substantial population growth, which is rapidly increasing the number of patients
Keywords: Sub-Saharan Africa; Cancer; Children